Solidago gigantea plants from nonnative ranges compensate more in response to damage than plants from the native range. Issue 9 (September 2016) - Liao, Huixuan; Gurgel, Priscila C. S.; Pal, Robert W.; Hooper, David; Callaway, Ragan M.
Abstract: Resistance and tolerance are two ways that plants cope with herbivory. Tolerance, the ability of a plant to regrow or reproduce after being consumed, has been studied less than resistance, but this trait varies widely among species and has considerable potential to affect the ecology of plant species. One particular aspect of tolerance, compensatory responses, can evolve rapidly in plant species; providing insight into interactions between consumers and plants. However, compensation by invasive species has rarely been explored. We compared compensatory responses to the effects of simulated herbivory expressed by plants from seven Solidago gigantea populations from the native North American range to that expressed by plants from nine populations from the nonnative European range. Populations were also collected along elevational gradients to compare ecotypic variation within and between ranges. Solidago plants from the nonnative range of Europe were more tolerant to herbivory than plants from the native range of North America. Furthermore, plants from European populations increased in total biomass and growth rate with elevation, but decreased in compensatory response. There were no relationships between elevation and growth or compensation for North American populations. Our results suggest that Solidago gigantea may have evolved to better compensate for herbivory damage in Europe, perhaps in response to a shift to greater proportion of attack from generalists. Our results also suggest a possible trade‐off between rapid growth and compensation to damage in European populations but not in North American populations.